Problems and needs faced by Pakistani university students when speaking English: A needs analysis approach - Kumar, Om; Prof. Dr. Mansoor Ahmed Channa; Aleksandrova, Oksana Ivanovna; Mansoor Ahmed Channa, Ghulam Akbar (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This quantitative study investigated the problems and needs of English-speaking skills among science faculty students at Quaid-e-Awam University of Engineering, Science and Technology, Nawabshah, Pakistan. A sample of 250 students from various science departments was surveyed using a well-structured questionnaire. The findings revealed that a significant portion of the students faced difficulties in understanding and using general vocabulary, adapting their language skills to diverse situations, expressing themselves effectively in conversations, conveying complex ideas, and maintaining both short and long conversations. These challenges cut across various age groups and interaction contexts. The study also highlighted that students perceived needs for improvement in several dimensions of their communication skills, including vocabulary usage, adaptability, interaction with different audiences, conveying intricate ideas, and employing technical language. The respondents expressed a strong desire to enhance their speaking abilities, particularly in professional and social settings.